The Long Shadows of the Manifesto of the Communist Party - Kuljić, Todor Đ. (Sociološki pregled, 2018)
Why is the Manifesto of the Communist Party present today? It recognized the revolutionary globalization dynamics of capitalism, anti-capitalism was considered, there was no defeatism, there was a clear fence of various reactionary socialisms and philanthropy, the relationship between necessity and freedom was defned in a new way and the melodrama of the lef was avoided.Keywords: Manifesto of the Communist Party, capitalism, anti-capitalism, defeatism, melodrama